The Data Acquisition System for a Kinetic Inductance Detector. Issue 8 (December 2015) - Branchini, P; Budano, A; Capasso, L; Marchetti, D
Abstract: The Data Acquisition System (DAQ) and the Front-End electronics for an array of Kinetic Inductance Detectors (KIDs) are described. KIDs are superconductive detectors, in which electrons are organized in Cooper pairs. Any incident radiation could break a pair generating a couple of quasi-particles that increase the inductance of the detector. The DAQ system we developed is a hardware/software co-design, based on state machines and on a microprocessor embedded into an FPGA. A commercial DAC/ADC board is used to interface the FPGA to the array of KIDs. The DAQ system generates a Stimulus signal suitable for an array of up to 128 KIDs. Such signal is up-mixed with a 3 GHz carrier wave and it then excites the KIDs array. The read-out signal from the detector is down-mixed with respect to the 3 GHz sine wave and recovered Stimulus is read back by the ADC device. The microprocessor stores read out data via a PCI express bus (PCIe) into an external disk. It also computes the Fast Fourier Transform of the acquired read out signal: this allows extrapolating which KID interacted and the energy of the impinging radiation. Simulations and tests have been performed successfully and experimental results are presented.